Analisis Studi Literatur Ekspolarasi Algoritma Pemrograman Mahasiswa Pendidikan Matematika Di Era Society 5.0 Dengan Bibliometrik - Nabila Rizki Aprilia; Yahfizham Yahfizham (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Information technology is advancing increasingly rapidly, especially in the era of society 5.0. Manual implementation has almost disappeared due to technological advances in programming. Today's activities or jobs tend to emphasize us being experts in using computers. In the era of society 5.0, logical thinking is very necessary in understanding the elements of combining mathematics and computer programming algorithms because the two are interrelated. The literature analysis method used in writing this article is to determine the actualization of this programming algorithm. The collection of this article was searched by searching books and several previous articles which were then developed by developing the titles of previous articles using bibliometric methods. So it is hoped that the development of technological science can run smoothly with the participation of programming algorithms in it so that mathematics education students are able to improve the quality of the combination of technological and mathematical sciences in the era of society 5.0.